Ponatinib vs. asciminib in post–second-generation tyrosine kinase inhibitor therapy for chronic-phase chronic myeloid leukemia: a matching-adjusted indirect comparison - Garcia-Gutierrez, Valentin; Huang, Fei; Ashaye, Ajibade; Dalal, Mehul; Laliman-Khara, Victor; Breccia, Massimo; Rutherford, Megan; Moradian, Hoora; Patos, Petros; Jabbour, Elias Joseph (Frontiers in Oncology, 2024)
BackgroundPonatinib and asciminib are approved for third-line therapy in chronic-phase chronic myeloid leukemia (CP-CML) and are the only drugs approved for patients with the T315I mutation in the United States. In Europe, only ponatinib is approved for patients with the T315I mutation.MethodsClinical trials evaluating ponatinib or asciminib in patients with relapsed and refractory (R/R) CP-CML who failed one or more second-generation TKIs or had the T315I mutation were identified in a systematic review of medical literature databases. A matching-adjusted indirect comparison (MAIC) analysis with individual patient-level data with ponatinib was used to balance baseline characteristics between ponatinib and asciminib groups. After matching, the response rate was calculated using the MAIC weight for each patient and the difference in response rate was calculated using a two-independent proportion Z-test. Cumulative rates of BCR::ABL1IS ≤1% and major molecular response (MMR) in patients without baseline response were compared. Patients were further stratified by T315I mutation status.ResultsThe MAIC included four trials (ponatinib: NCT02467270, NCT01207440; asciminib: NCT02081378, NCT03106779). In patients without baseline response of BCR::ABL1IS ≤1%, the adjusted BCR::ABL1IS ≤1% rate difference with ponatinib vs. asciminib was 9.33% (95% confidence interval [CI]: 0.79%–17.86%; adjusted MMR rate difference: 6.84% [95% CI: −0.95%–14.62%]) by 12 months in favor of ponatinib. In patients with the T315I mutation, adjusted BCR::ABL1IS ≤1% rate difference with ponatinib vs. asciminib was 43.54% (95% CI: 22.20%–64.87%; adjusted MMR rate difference: 47.37% [95% CI: 28.72%–66.02%]) by 12 months.ConclusionAfter key baseline characteristics adjustment, cumulative BCR::ABL1IS ≤1% and MMR rates were statistically higher with ponatinib than asciminib in patients without a baseline response in most of the comparisons by 12 months. Favorable efficacy outcomes observed in ponatinib vs. asciminib were consistently stronger in the T315I mutation subgroup.